The role of nafamostat mesylate anticoagulation in continuous kidney replacement therapy for critically ill patients with bleeding tendencies: a retrospective study on patient outcomes and safety - Taeil Kim; Dong Eon Kim; Eun Mi Jo; Yeji Lee; Da Woon Kim; Hyo Jin Kim; Eun Young Seong; Sang Heon Song; Harin Rhee (The Korean Society of Nephrology, 2024)
Background Continuous kidney replacement therapy (CKRT) is crucial in the management of acute kidney injury in intensive care units (ICUs). Nonetheless, the optimal anticoagulation strategy for patients with bleeding tendencies remains debated. This study aimed to evaluate patient outcomes and safety of nafamostat mesylate (NM) compared with no anticoagulation (NA) in critically ill patients with bleeding tendencies who were undergoing CKRT. Methods This retrospective study enrolled 2,313 patients who underwent CKRT between March 2013 and December 2022 at the third affiliated hospital in South Korea. After applying the exclusion criteria, 490 patients were included in the final analysis, with 245 patients in the NM and NA groups each, following 1:1 propensity score matching. Subsequently, in-hospital mortality, incidence of bleeding complications, agranulocytosis, hyperkalemia, and length of hospital stay were assessed. Results No significant differences were observed between the groups regarding the lengths of hospital and ICU stays or the incidence of agranulocytosis and hyperkalemia. The NM group showed a smaller decrease in hemoglobin levels during CKRT (-1.90 g/dL vs. -2.39 g/dL) and less need for blood product transfusions than the NA group. Furthermore, the NM group exhibited a survival benefit in patients who required transfusion of all three blood products. Conclusion NM is an effective and safe anticoagulant for CKRT in critically ill patients, especially those requiring transfusion of all three blood products. Although these findings are promising, further multicenter studies are needed to validate them and explore the mechanisms underlying the observed benefits.